The status of hygienic practices of small-scale poultry slaughterhouse in Thailand: An ecohealth approach - Chotinun, S. (Chiang Mai University, 2015)
Salmonella is pathogen of many mammalian species and it is one of the most important bacteria that cause food borne illness worldwide. Salmonella spp. can be commonly found in raw poultry and meat. Eggs, agricultural products, processed foods, raw milk and raw milk products and contaminated water also have been implicated in human salmonellosis. In Thailand, Salmonella was found to be the second largest cause of food poisoning, following rotavirus. Furthermore, antimicrobial-resistant strains of Salmonella spp. has been reported in many parts of the world. The importance of the resistance is that the bacteria acquire their resistance in the animal host before being transmitted to human through food chain. This may result treatment failures in human when applying antimicrobial agents to treat human salmonellosis. This study aimed to elucidate the status of small scale poultry slaughterhouses and their affect to ecological and health in the community in order to sustainably enhance hygiene and functioning of small scale poultry slaughterhouses in Northern Thailand. Initial steps included the identification of key stakeholders associated with the meat production chain, development of a research framework, and design of a methodology based on stakeholder consultations. The framework and methodology combine issues in five major areas: (1) public health, (2) socioeconomics, (3) policy, (4) veterinary medicine, and (5) communities and the environment. Consequently, a total of 41 small-scale poultry slaughterhouses were visited during the period from July 2011 to May 2012. Data on the current status of the slaughterhouses regarding productivity, economic status, hygienic management, and opportunities and challenges faced in improving the plants and following the DLD slaughterhouse regulations, were collected using a structured questionnaire and interviews. In addition, a checklist, which was developed based on the DLD regulations, was used for triangulation. In addition, a microbiological risk assessment approach was employed to detect Salmonella contamination in meat processing facilities. The microbial risk assessment was combined with stakeholder perceptions to provide an overview of the existing situation, as well as to identify opportunities for upgrading slaughterhouses in order to more effectively address matters of food safety, processing, and government licensing. The results of this study demonstrated that the developed conceptual framework could elucidate the complex factors limiting small-scale slaughterhouse improvement including a lack of appropriate enabling policies and an apparent absence of feasible interventions for improvement. Unhygienic slaughterhouse management was reflected in the incidence of Salmonella contamination. The prevalence of Salmonella spp. in live poultry, carcasses, waste water, and soil around processing plants were 3.17%, 7.32%, 21.27% and 29.27%, respectively. Moreover, the bacteria could be isolated from each point of slaughter lines. Eighteen different serotypes were identified, the most common being Corvallis (15.19%), followed by Rissen (13.92%), Hadar (12.66%), Enteritidis (10.13%), [I. 4,5,12 : i : -], Stanley, and Weltevreden (8.86%). Tests revealed that 68.35% of the Salmonella spp. were resistant to at least one antimicrobial while 50.63% showed multiple drug resistance (MDR). Specifically, 44.30% of Salmonella was resistant to nalidixic acid, followed by streptomycin (41.77%), ampicillin (34.18%), tetracycline (34.18%), and sulfamethoxazole/trimethoprim (20.25%). Policy advocacy was implemented through meeting with policy-level DLD officer responsible for slaughterhouse control in Thailand. The instruction including blueprint and feasible criteria of good practice of small scale poultry slaughterhouse was developed and then tested of microbiological quality of the meat. The results showed that Coliform bacteria and total bacteria count in meat after implementation was lower than that before implementation. It could be concluded that there is potential for the use of an Ecohealth approach to address critical problems and it’s solving at the interface of rural development and public health. The findings of this study could serve as a model for transdisciplinary studies and interventions related to other similar complex challenges.